2017
DOI: 10.2169/internalmedicine.56.7196
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose Co-transporter 2 Inhibitors Reduce the Abdominal Visceral Fat Area and May Influence the Renal Function in Patients with Type 2 Diabetes

Abstract: Objective and Methods An SGLT2 inhibitor (ipragliflozin, dapagliflozin, luseogliflozin, tofogliflozin, or canagliflozin) was administered to 132 outpatients with type 2 diabetes mellitus with or without other antidiabetic drugs for 6 months to evaluate its efficacy, the incidence of adverse events, and its influence on the renal function. Results The patient's mean glycated hemoglobin level significantly improved from 7.52±1.16% to 6.95± 0.98% (p<0.001). The body weight of the patients was significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 24 publications
4
29
1
2
Order By: Relevance
“…SGLT2 inhibitors, such as dapagliflozin, have been shown to improve glomerular hyperfiltration and blood pressure [10, 11], as add-ons to their action on blood glucose and glycated hemoglobin levels. The renoprotective effect of dapagliflozin in diabetic patients is still discrepant [13, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2 inhibitors, such as dapagliflozin, have been shown to improve glomerular hyperfiltration and blood pressure [10, 11], as add-ons to their action on blood glucose and glycated hemoglobin levels. The renoprotective effect of dapagliflozin in diabetic patients is still discrepant [13, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Dapagliflozin also improves insulin sensitivity and β-cell functions [8, 9], decreases body weight and lowers systolic blood pressure independently from insulin secretion or action [10]. Clinical data show that dapagliflozin lowers the estimated glomerular filtration rate [11] and then slows the progression of DN. It is also reported that dapagliflozin improves DN not only by lowering blood glucose but also by inhibiting inflammation and oxidative stress in db/db mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Canagliflozin is a SGLT2 inhibitor that offers an anti-diabetic effect by increasing urinary glucose excretion equates to a loss of approximately 308-476 calories per day [9]. While initial weight loss may reflect fluid loss due to osmotic diuresis, weight loss by canagliflozin is largely result of reduction of subcutaneous and visceral fat [10,11]. Multiple studies have demonstrated that treatment with canagliflozin result in significant reductions of HbA1c from baseline by -0.58% and -1.03% and in body weight by -3.3% and -4.4% after 52 weeks with 100 and 300 mg, respectively, in patients with diabetes [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Japanese patients, SGLT2 inhibitor-associated body fat reduction has been examined only in short-term (≤6 months) studies [2]. Therefore, we investigated long-term effects of SGLT2 inhibitor on body fat and liver function in Japanese patients with obese type2 diabetes (T2D).…”
Section: Introductionmentioning
confidence: 99%
“…Ipragliflozin significantly decreased visceral adipose tissue in 4-week observation in 25 Japanese T2D patients [10]. Visceral fat area was significantly reduced in 6-month observation of 64 diabetic patients [2]. However, obesity is difficult to treat as many subjects regain weight after temporary weight loss [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%